Diversity and molecular phylogeny of planktonic freshwater cyanobacteria from selected aquaculture ponds - Florence, Laiping. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study was designed to develop rapid detection technique to detect the potential cyanotoxins producers in aquaculture ponds. Another aim of this study was to determine the relationships between all cyanobacteria strains isolated from freshwater aquaculture ponds in Kota Marudu, Sabah and Indegenous Fisheries Research and Production Centre (IFRPC), Tarat Serian Saawak. Five genes were used in detection of cyanobacteria and toxin-producing cyanobacteria in aquaculture ponds while two genes (Partial 16s rRNA and phycocyanin genes) wee used in determining the relationship of selected cyanobacteria isolates from aquaculture ponds in Kota Merudu and Serian. The relationships of the selected cyanobacteria based on both genes were determined by constructing the phylogenetic trees using neighbour-joining, maximum parsimony, maximum likelihood and Bayesian methods.